Lower HIV provirus levels are associated with more APOBEC3G protein in blood resting memory CD4+ T lymphocytes of controllers in vivo. - Mariapia De Pasquale (PLoS ONE, 2013)
Immunodeficiency does not progress for prolonged periods in some HLA B57- and/or B27-positive subjects with human immunodeficiency virus type 1 (HIV) infection, even in the absence of antiretroviral therapy (ART). These "controllers" have fewer HIV provirus-containing peripheral blood mononuclear cells than "non-controller" subjects, but lymphocytes that harbor latent proviruses were not specifically examined in studies to date. Provirus levels in resting memory cells that can serve as latent reservoirs of HIV in blood were compared here between controllers and ART-suppressed non-controllers. APOBEC3G (A3G), a cellular factor that blocks provirus formation at multiple steps if not antagonized by HIV virion infectivity factor (Vif), was also studied. HLA-linked HIV control was associated with less provirus and more A3G protein in resting CD4+ T central memory (Tcm) and effector memory (Tem) lymphocytes (provirus: p = 0.01 for Tcm and p = 0.02 for Tem; A3G: p = 0.02 for Tcm and p = 0.02 for Tem). Resting memory T cells with the highest A3G protein levels (>0.5 RLU per unit of actin) had the lowest levels of provirus (<1,000 copies of DNA per million cells) in vivo (p = 0.03, Fisher's exact test). Using two different experimental approaches, Vif-positive viruses with more A3G were found to have decreased virion infectivity ex vivo. These results raise the hypothesis that HIV control is associated with increased cellular A3G that may be packaged into Vif-positive virions to add that mode of inhibition of provirus formation to previously described adaptive immune mechanisms for HIV control.